(untitled) (Jurnal Manajemen Perhotelan, 2008)
Internet and website is an important tool for business marketing without any geographical or time constraints. Therefore, hotel website providers have to be able to meet customers’ expectations. This research attempts to compare the expectation and perception of customers toward the dimension of website of five stars hotels in Surabaya, which are facilities information, reservation information, contact information, website management and surrounding area information. The result shows that there are a significant gap between the expectation and the perception of customers. Abstract in Bahasa Indonesia : Internet dan website merupakan sarana pemasaran tanpa batasan geografis dan waktu. Penyedia website hotel dituntut mampu menyediakan website dengan isi yang sesuai kebutuhan konsumen. Penelitian ini bertujuan mengukur perbedaan antara harapan dan persepsi konsumen terhadap dimensi website hotel bintang lima di Surabaya, yaitu informasi fasilitas, informasi customer contact, informasi reservasi, informasi area sekeliling hotel, dan manajemen website. Hasil penelitian menunjukkan bahwa terdapat gap antara harapan dan persepsi konsumen terhadap dimensi website hotel bintang lima di Surabaya. Kata kunci: harapan, persepsi, konsumen, website, hotel bintang lima.